2022
DOI: 10.1177/11782218221106797
|View full text |Cite
|
Sign up to set email alerts
|

Is There an Association Between Salivary Cortisol and Dropping Out of Inpatient Substance Addiction Treatments? A Prospective Repeated Measures Study

Abstract: Several studies have found an association between salivary cortisol levels and dropping out of inpatient substance addiction treatment programs. The results are mixed due to variations in the study design and the lack of standardized routines for cortisol assessment. The aim of this study was to investigate whether there was (1) an association between salivary cortisol levels and dropping out from inpatient substance addiction treatments; (2) higher predictive validity for dropout in one of the cortisol indexe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 78 publications
1
2
0
Order By: Relevance
“…Interestingly, the multi-ancestry meta-analysis revealed pathways of relevance to the neuroimaging findings in AUD ( 36 ) and to our cell type analysis, including the substantia nigra, frontal cortex and nucleus accumbens. The association with the hypothalamus, a region that regulates liquid intake, could be related to the consumption component of AUD, in line with our previous findings associating hypothalamus with both alcohol consumption and AUD loci ( 33 ) and with experimental data regarding altered hypothalamic-pituitary-adrenal axis after chronic alcohol exposure ( 37 ). The current findings further illustrate the complementarity of the tissue-level and cell-level bioinformatic approaches to open therapeutic avenues in AUD ( 38 , 39 ).…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, the multi-ancestry meta-analysis revealed pathways of relevance to the neuroimaging findings in AUD ( 36 ) and to our cell type analysis, including the substantia nigra, frontal cortex and nucleus accumbens. The association with the hypothalamus, a region that regulates liquid intake, could be related to the consumption component of AUD, in line with our previous findings associating hypothalamus with both alcohol consumption and AUD loci ( 33 ) and with experimental data regarding altered hypothalamic-pituitary-adrenal axis after chronic alcohol exposure ( 37 ). The current findings further illustrate the complementarity of the tissue-level and cell-level bioinformatic approaches to open therapeutic avenues in AUD ( 38 , 39 ).…”
Section: Discussionsupporting
confidence: 91%
“…Procedures for sampling and analyzing cortisol were the same as reported in Bohle et al 52 In short, all sampling was performed over two consecutive days, 4 times a day for each timepoint (T1-4). Samples were gathered using a saliva collection device (Sarstedt Nümbrecht, Germany) that consisted of a cotton swab and a sampling vessel.…”
Section: Methodsmentioning
confidence: 99%
“… 51 A limitation of previous research is the lack of repeated measures and a standardized protocol for sampling and calculation of salivary cortisol measures. Of the few prospective studies, 27 , 38 , 42 , 52 a study conducted by Jaremko et al 38 is of special interest due to the fact that it combined biological and psychosocial variables when assessing dropout risk. This study found that abnormal cortisol measures increased dropout risk and elevated psychological distress and poor treatment engagement in those who dropped out.…”
Section: Introductionmentioning
confidence: 99%